(untitled) (Música Hodie, 2024)
The main objective of this article is to investigate the effectiveness of utilizing a supplementary learning model through Massive Open Online Courses (MOOCs) for the reform of traditional Chinese music education in higher education institutions in China. The study involved 314 fourth-year students from three higher education institutions, with an average age of 22.22 years (SD = 0.45). Two self-report scales were employed as instruments. The research demonstrated a significant improvement in the assimilation of traditional Chinese music among students who integrated MOOCs into their coursework, with an increase of 8.2 points. In the experimental group, all key indicators significantly increased: student satisfaction rose by 8.4 points, academic performance increased by 6.8 points, and interest in further study increased by 9.25 points. The enhancement of all examined indicators in the experimental group indicates the positive impact of MOOCs on musical education and cultural capital, confirming the effectiveness of a synergistic approach. Thus, the research results underscore the potential of online courses in enriching the educational process and expanding access to cultural heritage. The scholarly value of this research is evident in confirming the effectiveness of integrating MOOCs to enhance the study of traditional Chinese music, serving as a foundation for further development of educational methodologies and technologies. The practical significance lies in the potential application of the results to improve the quality of musical education in higher education institutions and broaden global access to cultural heritage. Funding: Basic scientific research business project of Heilongjiang Provincial Department of Education, ‘Research on the inheritance and development of Daur music in Nenjiang River from the perspective of intangible cultural heritage’, Subject No: 145209168